Introduction to the Special Issue: New Methods in Exposure Therapy. (March 2013) - McKay, Dean; Whiteside, Stephen P. H.
Exposure-based interventions have been shown to significantly reduce anxiety and avoidance. The efficacy of the approach is robust, and recent efforts have been made to expand the use of exposure as well as identify more effective ways to implement the procedure. This article introduces the special issue devoted to recent novel approaches to the dissemination and implementation of exposure.